2018
DOI: 10.1002/jcc.25603
|View full text |Cite
|
Sign up to set email alerts
|

First Principles Calculations Toward Understanding SERS of 2,2′‐Bipyridyl Adsorbed on Au, Ag, and Au–Ag Nanoalloy

Abstract: First principles electrodyanmics and quantum chemical simulations are performed to gain insights into the underlying mechanisms of the surface enhanced Raman spectra of 22BPY adsorbed on pure Au and Ag as well as on Au-Ag alloy nanodiscs. Experimental SERS spectra from Au and Ag nanodiscs show similar peaks, whereas those from Au-Ag alloy reveal new spectral features. The physical enhancement factors due to surface nano-texture were considered by numerical FDTD simulations of light intensity distribution for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 50 publications
0
18
0
Order By: Relevance
“…This model was named Ag 20 -B. The Au 10 Ag 10 nanoalloy geometry was based on the lowest energy isomer presented in ref . Finally, the M 58 clusters were obtained by adapting the Au 58 equilibrium structure presented in ref .…”
Section: Methodsmentioning
confidence: 99%
“…This model was named Ag 20 -B. The Au 10 Ag 10 nanoalloy geometry was based on the lowest energy isomer presented in ref . Finally, the M 58 clusters were obtained by adapting the Au 58 equilibrium structure presented in ref .…”
Section: Methodsmentioning
confidence: 99%
“…For example, in a similar way nanosponges can be produced from co-sputtered noble-metal films forming nano-alloys with engineered permittivity as demonstrated for Au-Cu-Ag [56]. Along with plasmonic hot spot engineering, local potential defined by the nearest atomic composition was shown to modify physical and chemical adsorption of the analyte molecules affecting their characteristic SERS and SEIRA signals and sensor performance [57]. Insights into formation of metallic glasses and high entropy alloys with even large number of constituent materials [58] will benefit from a nanoscale control of re-melting and phase-explosions demonstrated in this work.…”
Section: Discussionmentioning
confidence: 98%
“…More specifically, non-uniform deposition of the Au material above the surface textures provided decoration of Ag nanospikes with Au nanoclusters (see Figure 2e), further boosting plasmonic response of the spallative textures [37]. Additionally, density functional theory calculations recently showed that nanoscale alloying of SERS active metals can support SERS enhancement [41]. Finally, the Au coating rendered the central site hydrophilic.…”
Section: Properties Of Sers-active Site and Analyte-enrichment Systemmentioning
confidence: 98%